2008
DOI: 10.1103/physrevlett.101.233401
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Study of Carbon Monoxide Solvated with Helium Atoms

Abstract: High resolution microwave and millimeter-wave spectra of HeN-CO clusters with N up to 10, produced in a molecular expansion, were observed. Two series of J = 1-0 transitions were detected, which correspond to the a-type and b-type J = 1-0 transitions of He1-CO. The B rotational constant initially decreases with N and reaches a minimum at N = 3. Its subsequent rise indicates the transition from a molecular complex to a quantum solvated system already for N = 4. For N > or =6, the B value becomes larger than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 33 publications
9
78
0
Order By: Relevance
“…The turn around of B with N was observed for the first time in 2003, with N 2 O as the dopent molecule. Since then, along with OCS [14] and N 2 O [2,3,[15][16][17][18][19][20], the vibrational and rotational spectra of several other molecules, e.g., HCCCN [9], CO 2 [31], CO [32], etc., for very small N, have also been reported.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The turn around of B with N was observed for the first time in 2003, with N 2 O as the dopent molecule. Since then, along with OCS [14] and N 2 O [2,3,[15][16][17][18][19][20], the vibrational and rotational spectra of several other molecules, e.g., HCCCN [9], CO 2 [31], CO [32], etc., for very small N, have also been reported.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…We note that the ∆J = 0, ±2 selection rule would be relaxed for symmetric top molecules and may indeed indicate the involvement of C 2 H 2 -(He) n clusters. However, the good match of these transitions with multiples of the b constant of free C 2 H 2 is difficult to explain considering that in other molecule-helium complexes such lines are always shifted 90 .…”
Section: Time-resolved Alignment and Fourier Transformationmentioning
confidence: 99%
“…Such experiments are directed on the detection of a superfluid response of molecular rotation in helium clusters [6,7]. It was shown that the lighter probe molecules allow one to measure the effective inertia of He clusters while maintaining a maximum…”
Section: Introductionmentioning
confidence: 99%